Formation the complex of organizational components of production system in agricultural enterprises - Лозинська, Інна Віталіївна (Technology audit and production reserves, 2015)
Conducted researches aimed to identify and describe the main components of the production system of agricultural enterprises in meat and dairy cattle, which effective operation can significantly improve the economic stability of enterprises in the modern business environment. The process of forming and achieving economic impact of the production system agricultural enterprises, the quality of which is determined by optimal combination of all elements and stages of the production process (people, vehicles and objects of labor, and the main, auxiliary and natural processes) in space and time. It was established, that the stability of the system is influenced by various factors. Thus, for example, one of the selected unit factors affect market infrastructure, the intensity and volume of raw material purchasing, contracts with contractors, the reaction of consumers for products and more. Therefore, have an influence of these factors, you can achieve system stability.